Communication strategies in multi-ethnic societies: a comparative analysis of the approaches of Kazakhstan and Russia - Nechaeva Е.Л.; Kayupova Ф.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
In the context of globalization, accompanied by growing ethnic diversity, the management of multi-ethnic societies is becoming one of the key tasks of public policy. Of particular importance is the development of effective communication strategies aimed at strengthening civic identity, preventing ethnic conflicts and increasing the level of trust in government. The article examines theoretical approaches to the formation of such strategies, their principles and methods of implementation. Using the example of Russia and Kazakhstan, various models of strategizing are analyzed, demonstrating how to adapt interethnic policy to the unique social, cultural and historical characteristics of each society, ensuring the harmonization of interethnic relations and sustainable development of the state. Particular attention in the study is paid to the institutionalization of interethnic interaction, which includes the creation of sustainable and effective structures that promote dialogue between different ethnic groups. This involves their active participation in the political and public life of the country, which strengthens social stability. The work identifies successful practices aimed at harmonizing interethnic relations. It is emphasized that the key factors of successful strategizing are inclusiveness, openness of the authorities to dialogue and consideration of historical and cultural characteristics of the regions. The analysis of the proposed approaches and models of strategizing demonstrates the importance of a comprehensive and systemic approach that takes into account not only socio-cultural, but also economic and political aspects of interethnic interaction. The solutions considered in this work are highly adaptable, which makes them applicable in a variety of contexts.